Predictive power of implied volatility of structured call warrants: evidence from Singapore - Murad Samsudin, Najmi Ismail; Mohamad, Azhar; Mohammad Sifat, Imtiaz; Hamid, Zarinah (John Wiley & Sons, Ltd., 2020)
This paper examines the information content of implied volatility of structuredcall warrants in the Singapore Stock Exchange. The study is among the first to examine the implied volatility of equity options (structured call warrants) outside the United States. Using a daily dataset for 252 trading days between August 1, 2014 and July 31, 2015, we test whether implied volatility is an unbiased estimate of realized volatility (RV). In other words, we ask whether implied volatility contains information on future RV, and scrutinize the efficiency of implied volatility and its predictive power compared to historical volatility (HV). Our findings suggest that although implied volatility does contain some relevant information about future volatility, it remains a biased forecast of RV. The efficiency of implied volatility is trivial, and its predictive power is not superior to HV.